The effect of corrosion defects on burst pressure of pipelines - Khairul Anwar, Ibrahim (2012)
The predictions of pipeline burst pressure in the early stage are very importance in order to provide assessment for future inspection, repair and replacement activities. The failure of oil and gas pipelines contribute to economic implications and also constitute a serious hazards to the environment due to leakage. This thesis deals with the study on the effect of corrosion defect on the burst pressure of pipelines for API 5L X42 steel. The objectives for this project are to determine the burst pressure of corroded pipelines using Finite Element Analysis (FEA) and to compare the results with the available pipelines design code. This project implicates analysis of the API X42 steel by using MSC Patran 2008 r1 software as pre-processor and MSC Marc 2008 r1 software as a solver. A quarter of pipe was simulated by fully applying the symmetrical condition. The pipe is modeled in 3-D with outer diameter of 60 mm, wall thickness of 6 mm and different defect parameters. In this analysis, stress modified critical strain used as failure criterion to predict the failure of defective pipe. Result shows that the burst pressure decreases when both defect depth and length increases. The defect depth appear as a most influence parameter that affect the burst pressure. The circumferential extent has a less influence on the burst pressure. The results have been compared to available design codes for corroded pipelines such as ASME B31G, Modified ASME B31G and DNV RP F101. Comparison with available design codes have shown that FEA burst pressure gives higher values compare to codes. From the results, ASME B31G gives the lowest values than other codes.